Letter from Svante Arrhenius to Georg Bredig, November 1895 - Arrhenius, Svante (1895)
Svante Arrhenius (1859-1927) writes to Georg Bredig (1868-1944) to update him on his personal life, professional endeavors, and his laboratory.
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Chemists; Ostwald, Wilhelm, 1853-1932; Nobel Prize winners